FAKTOR PENYEBAB TERJADINYA GUGAT CERAI DI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Astuti, Inda Puji Astuti Puji (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is motivated harmonization households always ends with a divorce by the wife. As in the case of divorce occurred in Pangkalan Kuras district, the case is seen from the quantity is high. The issue raised in this research is the factors that cause the occurrence of divorce in Pangkalan Kuras district, Pelalawan regency. This research aims to determine the factors that cause the occurrence of divorce in Pangkalan Kuras district, Pelalawan regency. The source for this research was people that involved in a case of divorce that occurred in 2013, there were 50 respondents. The technique that used in this research was a total sampling technique, so that it was just 40 respondents. The data were collected through observation, interview, questioner, literature study and documentation and it was been analyzed by using descriptive qualitative way. The result of this research can be concluded that the cause of divorce in Pangkalan Kuras district, Pelalawan regency is because of a husband left his wife for a long time. It was because the survey showed that 32 respondents or 80% said that. Contrary with this, based on hypothesis of the author that assumed the causes of divorce in Pangkalan Kuras district, Pelalawan regency were the economic factor and a third person wer rejected. Keywords: factors, causes, accountability, divorce